BTV antibody longevity in cattle five to eight years post BTV-8 vaccination. Issue 20 (6th May 2019) - Ries, Christina; Beer, Martin; Hoffmann, Bernd
Abstract: The Bluetongue virus serotype −8 (BTV-8) epizootic in Germany (2006–2008) was successfully eradicated, essentially by the massive application of commercially available inactivated BTV-8 vaccines. While a six-year antibody longevity of BTV antibodies post BTV-8 vaccination in cattle has been described previously, our study investigated the BTV-8-vaccine antibodies in cattle for up to eight years. In total, 157 bovine serum samples were analysed for the presence of group-specific BTV antibodies in both a commercial cELISA, and a BTV-8- specific serum neutralization test. A robust number of cattle were seropositive for group- and serotype-specific neutralising antibodies for five or more years. In selected animals, born and vaccinated in 2009 or later, the presence of BTV antibodies for up to eight years post BTV-8 vaccination could be confirmed. Our data also show, that booster vaccination prolonged the antibody longevity of vaccine-induced antibodies and the number of serologically positive cattle.